System of decoration of the Salle de Balle castle of Fontainebleau - Романенкова, Ю.В. (Proceedings of National Aviation University (archive), 2012)
This article is dedicated to the problem of decor of French palace interiors of XVI century, new principle of their decoration during the period of Mannerism, complex of art methods, that were characteristic for French and Italian artists. An accent is new principle of decoration of interiors of royal palaces by means of combination of frescos, wooden panels, stuccos elements and gilding.